G Green Marketing di Era Digital: Implikasi Green Subjective Norm dan Lifestyle terhadap Minat Pembelian Konsumen - Wenti Ayu; Muhardono, Ari; Wafa Khansa Fadhilah; Supajar Bayu Aji (Jurnal Ekonomi dan Bisnis, 2025)
This study focuses on consumer purchasing interest in green products, with the aim of the study being to test a model that presents the influence of green subjective norm and green lifestyle on purchase intention through social media marketing on green products that are currently trending in an environmentally friendly lifestyle (go green). This research uses a quantitative method with a conclusive research design through a causal approach, with an analysis technique using SEM PLS with Smart PLS devices. The study population includes the people of Pekalongan City, and the research was conducted through a non-probability sampling method in the form of accidental sampling with a sample of 100 respondents to represent consumer purchasing interest in green products. The results of the study showed that the green subjective norm and green lifestyle had a positive and significant effect on consumer purchasing interest. Social media marketing had a significant positive effect on consumer purchasing interest. Furthermore, the results showed that there was no significant positive effect between green subjective norm and green lifestyle on social media marketing. The results of the analysis found that the mediation variable social media marketing did not mediate the relationship between green subjective norm and purchase intention through social media marketing, but in the relationship between green lifestyle and purchase intention through social media marketing, the results mediated fully or were said to be significantly positive.